An instrumented large soil column to investigate climatic ground interaction. Issue 2 (14th March 2021) - Udukumburage, Rajitha Shehan; Gallage, Chaminda; Dawes, Les
Abstract : The field monitoring of the climatic-induced behaviour of the expansive soil has always been difficult, expensive and time consuming. The uncontrollability of the field boundary conditions and the difficulty in accurately measuring them have worsened the problem. As an alternative, the instrumented model set-ups are ideal for long-term monitoring of expansive soils since the laboratory compacted expansive soils become environmentally stabilised after few wet–dry cycles. There had been a very limited laboratory-based column set-ups for the observation of expansive soils under unsaturated conditions with an appropriate set of sensors embedded at known depths. The major difficulties associated with model tests are considerable boundary effect and sensor-to-soil area ratio due to the insufficient physical model dimensions. In this study, the research need for a laboratory model set-up with minimised boundary effects has been addressed by a large instrumented soil column, which could more closely represent environmentally stabilised soil. The current results depict the expected pattern for the variations of soil suction, volumetric water content and soil displacement under wetting and drying phenomenon, which accentuates the applicability of instrumented soil column for the investigation of climatic-induced expansive soil behaviour.